Supporting navigation using different types of spatial information : an experimental human factors study - Nixon, James Anthony Kidby (2008)
This thesis presents research which examines how the display of location-based information on a mobile device affects navigation. The research was informed by current literature and user research conducted with Nottinghamshire Fire and Rescue Services. Experimental results are explained in terms of Passini’s (1980) model of wayfinding. Design guidelines and a human-factors framework for mobile location-based services are also presented. Cognitive task analysis and semi-structured interviews were used to conduct a user requirement study with firefighters from Nottinghamshire Fire and Rescue Services. Following this study, an experimental programme was developed to test how different methods of presenting information and displaying different types of information affected navigation. Measurements included time taken to navigate a route, workload, perceived usability and perceived navigational ability. A small scale observational study examined user behaviour while navigating with GPS enabled information. Finally, a focus group was used to evaluate the results from the experimental work with Nottinghamshire Fire and Rescue Services. Qualitative studies suggest that firefighters could use mobile, location based information to enhance navigation in large incidents. This information should be easy to understand and act on, incurring the minimum of cognitive demand. To achieve these requirements, the type of information presented on a paper map should not simply be transferred directly to a mobile device but must be adapted. The type of information displayed must also take into account the environment to maximise navigation efficiency and minimise cognitive demand. In the inside environment, simplified information showing only main features such as staircases and route changes should be displayed. In the outside environment paths and a selection of large, permanent features such as buildings support navigation most effectively. Evaluation with the fire service indicates that firefighters concur with the results of the experimental program. Major areas of further research include collaborative designs involving multiple mobile services and further experimental work examining how the presentation of specific features affects navigation in the outside environment.